Predicting the Distribution of CO2 Impurities in Hydrocarbons: Seismic Reservoir Characterization in the Northern South Sumatera Basin - Rahmawati, Ricky; Wahidah, Wahidah; Alamsyah, M Noor; Hamdani, Dadan; Alamsyah, Andi (JURNAL GEOCELEBES, 2025)
An oil and gas field containing less than 50% carbon dioxide (CO₂) impurities is considered economically viable. This study focuses on the 'X' area, located in the northern part of the South Sumatra Basin, and evaluates the sensitivity of elastic parameters—specifically P-impedance and Vp/Vs ratio—to hydrocarbon presence. Additionally, the study assesses the distribution of sandstone reservoirs within the Lower Talang Akar Formation (LTAF) using seismic reservoir characterization methods, while also analyzing the spatial correlation of natural CO₂ impurities. Using data from 11 wells equipped with S-wave logs, a multi-attribute analysis was applied to predict reservoir properties in 57 additional wells. Sensitivity analysis of hydrocarbons, reservoir, and non-reservoir zones was then conducted using elastic log parameters. Seismic attributes such as variance and ant tracking were utilized to detect fault patterns and potential fractures. Moreover, Relative Acoustic Impedance maps—based on negative and minimum amplitude summations—were generated to visualize sandstone reservoir distribution and CO₂ impurity saturation derived from well tests. Results show that hydrocarbons exhibit greater sensitivity to the Vp/Vs ratio than to P-impedance, although sandstone reservoirs generally display low P-impedance values. Faults in the LTAF surface trend north-south, northwest-southeast, and northeast-southwest, with the highest density in the eastern region of area 'X'. Thick sandstone reservoirs are predominantly found in the northern, southern, western, and southeastern sectors. CO₂ saturation trends decrease westward, aligning with reservoir presence and fracture intensity. Zones with thick reservoirs and low CO₂ levels are identified as key targets for future exploration and development.